2018
DOI: 10.3390/md16110444
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bioactive Peptides from Meretrix meretrix Protect Caenorhabditis elegans against Free Radical-Induced Oxidative Stress through the Stress Response Factor DAF-16/FOXO

Abstract: The hard clam Meretrix meretrix, which has been traditionally used as medicine and seafood, was used in this study to isolate antioxidant peptides. First, a peptide-rich extract was tested for its protective effect against paraquat-induced oxidative stress using the nematode model Caenorhabditis elegans. Then, three novel antioxidant peptides; MmP4 (LSDRLEETGGASS), MmP11 (KEGCREPETEKGHR) and MmP19 (IVTNWDDMEK), were identified and were found to increase the resistance of nematodes against paraquat. Circular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Paraquat induced oxidative stress assay was conducted by incubating the worms for pretreatment with FA for 24 h [ 75 ]. Afterward, worms were transferred to fresh NGM plates containing 50 mM paraquat (Aladdin, Shanghai, China) at final concentration and FA.…”
Section: Methodsmentioning
confidence: 99%
“…Paraquat induced oxidative stress assay was conducted by incubating the worms for pretreatment with FA for 24 h [ 75 ]. Afterward, worms were transferred to fresh NGM plates containing 50 mM paraquat (Aladdin, Shanghai, China) at final concentration and FA.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 6 E, the results showed that sod-3 was up-regulated by SeP2 and SeP5, while ctl-1 was also up-regulated by SeP5. It has been reported that some antioxidants could increase the oxidative stress resistance through the activation of antioxidant related signaling pathways and sequentially up-regulate the expressions of their target genes such as sod-3 and cat-1, which might enhance the potential of anti-oxidative stress [ 44 , 45 , 46 ]. In agreement with these, the present results demonstrate that S. esculenta antioxidant peptides have a protective effect in oxidation-damaged worms, which is associated with the up-regulation expression of stress-related genes, suggesting that peptides alleviating oxidative stress are closely related to enhancing antioxidant activity in C. elegans .…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress caused by paraquat was performed with the wild-type worms as reported previously [ 31 ]. L1-stage worms were incubated in S medium fed with NA22 at 20°C until the L4 stage and put into a 96-well microplate containing NA22, ampicillin (100 μ g/mL), and FUDR (75 μ g/mL).…”
Section: Methodsmentioning
confidence: 99%